FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI MASYARAKAT PADA PROGRAM CITARUM HARUM DI DESA PADAMULYA KECAMATAN MAJALAYA KABUPATEN BANDUNG - Budi Kusumo, Rani Andriani; Rasmikayati, Elly; Waqi, Lutfi Ahmad (Agros Journal of Agriculture Science, 2024)
The Citarum River plays an important role for the people of West Java Province. However, the condition of the Citarum River continues to decline due to various problems that arise in the upstream and downstream parts of the river. In response, the government implemented the Citarum Harum program to address the environmental issues along the Citarum River basin. The success of this government-initiated program requires active participation from the community. This study aims to analyze the factors associated with the level of community participation in the Citarum Harum program in Padamulya Village, Majalaya District, Bandung Regency. A quantitative design with a survey technique was employed for this study. A total of 51 randomly selected residents of Padamulya Village constituted the respondents in this study. Data were analyzed through Spearman Rank correlation analysis. The results indicated that community awareness, ability, opportunities provided, perceived benefits, and the figure of the leader were positively correlated with the level of community participation. These results suggest the importance of maintaining and improving these factors as a means of increasing community participation in the Citarum Harum program.